2011
DOI: 10.1364/boe.2.002083
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence microspectroscopy as a tool to study mechanism of nanoparticles delivery into living cancer cells

Abstract: Lack of better understanding of nanoparticles targeted delivery into cancer cells calls for advanced optical microscopy methodologies. Here we present a development of fluorescence microspectroscopy (spectral imaging) based on a white light spinning disk confocal microscope with emission wavelength selection by a liquid crystal tunable filter. Spectral contrasting of images was used to localize polymer nanoparticles and cell membranes labeled with fluorophores that have substantially overlapping spectra. In ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 33 publications
1
23
0
Order By: Relevance
“…Since biological membranes are composed of dynamically condensed domains surrounded by fluid domains, it has been suggested that, above the CMC, alkyl phospholipids can insert into both kinds of phases: as monomers into the condensed phase and as a group of monomers into the fluid phase [32]. This is also in agreement with fluorescence microspectroscopy data, which show that lipophilic phospholipid fluorescent probe NBD-PC, where 7-nitrobenz-2-oxa-1,3-diazol-4-yl (NBD) is attached to a phosphatidylcholine phospholipid is immediately transferred into cells after addition of liposomes with higher than 1:1 ratio of perifosine to cholesterol, whereas liposomes with lower ratio do not interact with cells [26,33]. With electron paramagnetic resonance spectroscopy it was similarly shown that hydrophilic spin probe encapsulated in liposomes with lower than 1:1 ratio of perifosine to cholesterol does not enter cells, whereas starts entering cells immediately after incubation when it is encapsulated in liposomes with higher than 1:1 ratio of perifosine to cholesterol [34].…”
Section: Introductionsupporting
confidence: 72%
“…Since biological membranes are composed of dynamically condensed domains surrounded by fluid domains, it has been suggested that, above the CMC, alkyl phospholipids can insert into both kinds of phases: as monomers into the condensed phase and as a group of monomers into the fluid phase [32]. This is also in agreement with fluorescence microspectroscopy data, which show that lipophilic phospholipid fluorescent probe NBD-PC, where 7-nitrobenz-2-oxa-1,3-diazol-4-yl (NBD) is attached to a phosphatidylcholine phospholipid is immediately transferred into cells after addition of liposomes with higher than 1:1 ratio of perifosine to cholesterol, whereas liposomes with lower ratio do not interact with cells [26,33]. With electron paramagnetic resonance spectroscopy it was similarly shown that hydrophilic spin probe encapsulated in liposomes with lower than 1:1 ratio of perifosine to cholesterol does not enter cells, whereas starts entering cells immediately after incubation when it is encapsulated in liposomes with higher than 1:1 ratio of perifosine to cholesterol [34].…”
Section: Introductionsupporting
confidence: 72%
“…1. The system was built on an inverted microscope Nikon Eclipse TE 2000-E platform with a combination of a fluorescence unit CARV II spinning disk confocal module (BD Biosciences, Franklin Lakes, NJ, USA) that housed the excitation, dichroic and emission filters (BrightLine filters from Semrock, Rochester, NY, USA) as well as a multiple-hole spinning disk for the confocal imaging [33]. Objective lenses with 10× and 40× magnification were used in these experiments to provide the high magnification and the desired high spatial resolution.…”
Section: Confocal Fluorescence Microscopy Systemmentioning
confidence: 99%
“…However, both¯lter technologies su®er from the polarization-dependent property, which leads to poor light transmission e±ciency (approximately 40%) and the additional drivers make the imaging system more complex and expensive. 8,9 As a newly developed spectral selecting technique, TFTF has sharp edge cut-o®s and high out-of-band optical densities. But TFTF needs an array of thin¯lm tunable¯lters to cover a wide wavelength range, because each single TFTF has a limited bandwidth.…”
Section: Introductionmentioning
confidence: 99%